Formation and characterization of Ge1−x−ySixSny/Ge1−xSnx/Ge1−x−ySixSny double heterostructures with strain-controlled Ge1−x−ySixSny layers. (1st November 2017) - Fukuda, Masahiro; Yamaha, Takashi; Asano, Takanori; Fujinami, Syunsuke; Shimura, Yosuke; Kurosawa, Masashi; Nakatsuka, Osamu; Zaima, Shigeaki
Abstract: The formation of Ge1− x − y Si x Sn y /Ge1− x Sn x /Ge1− x − y Si x Sn y double heterostructures with strain-controlled Ge1− x − y Si x Sn y layers and their crystalline properties were investigated. We achieved the epitaxial growth of double heterostructures consisting of a Ge1− x Sn x layer with a Sn content of 9% sandwiched between compressive- or tensile-strained Ge1− x − y Si x Sn y layers. The strain sign of the Ge1− x − y Si x Sn y epitaxial layer influenced the crystallinity of the double heterostructures. Compressive-strained Ge1− x − y Si x Sn y layers provided double heterostructures with higher crystallinity than the tensile-strained ones. The magnitude of strain in the Ge1− x − y Si x Sn y layers also affected the surface roughness of the double heterostructures. Low surface roughness was achieved by decreasing the magnitude of strain in the Ge1− x − y Si x Sn y layers. Moreover, the strain sign and/or Si content in Ge1− x − y Si x Sn y influenced the thermal stability of the double heterostructures. Compressive-strained Ge1− x − y Si x Sn y and/or a low Si content in Ge1− x − y Si x Sn y improved the thermal stability of the double heterostructures to withstand annealing temperatures as high as 400 °C.